PENGARUH KEPEMIMPINAN, MODAL PSIKOLOGIS, DAN KEADILAN ORGANISASI TERHADAP KINERJA PEGAWAI - Mila Hariani; Didit Darmawan (Universitas Mahendradatta, 2025)
This study aims to analyze the effect of leadership, psychologicalcapital, and organizational justice on employee performance. Data were obtainedfrom 100 respondents working in manufacturing companies in Surabaya throughsurvey method and analyzed using multiple linear regression. The results showedthat the three independent variables have a significant influence on employeeperformance, with the largest contribution coming from leadership. Psychologicalcapital supports individual performance through strengthening self-efficacy,optimism, hope, and resilience, while organizational justice also strengthensemployee performance by contributing to the organization. This study suggeststhe development of transformational leadership programs, psychological capitaldevelopment training, and consistent justice policies to improve overall employeeperformance.